A new approach to solve linear programming problem with intercept values. Issue 4 (3rd July 2016) - Sumathi, P.
Abstract: Linear Programming (LP) finds many uses in business and industry, where a decision maker may want to utilize limited available resources in the best possible manner. Limited resources may include material, money, manpower, space and time. Linear programming provides various methods of solving such problems. This paper presents a new approach for selecting constraints in solving a linear programming problem. Here the intercept values are used to find out the equality constraints among the inequality constraints. This new method will be valid in achieving optimal solution.